2001
DOI: 10.1111/j.1740-8261.2001.tb00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Evaluation of Gallbladder Wall Thickness in Cats

Abstract: Ultrasonography of the gallbladder and biliary tract was performed on 42 cats: 22 clinically healthy cats (group A) and 20 cats with hepatobiliary disease and post mortem confirmation of gallbladder abnormalities (group B). The gallbladder wall was visible in 9 of 22 cats in group A and all 20 cats in group B. Additional gallbladder findings in group B included shape anomalies, biliary tract obstruction, wall thickening, polyps, neoplasia, and biliary sludge. Ultrasonographic evaluation of abdominal organs ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 21 publications
2
60
0
Order By: Relevance
“…13 In all five caracals, the wall of the gall bladder was clearly visualized, contrary to domestic cats and dogs in which it is poorly seen or not identified. 3,13 The mean gall bladder wall thickness in caracals (0.6 mm) measured within the reported range in domestic cats (0.4-0.9 mm) 7 but lower than the reported mean in cheetahs (1.1 mm). 4 Caracals had five characteristic ultrasonographic layers of the gastrointestinal tract similar to those of domestic cats 11 and dogs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…13 In all five caracals, the wall of the gall bladder was clearly visualized, contrary to domestic cats and dogs in which it is poorly seen or not identified. 3,13 The mean gall bladder wall thickness in caracals (0.6 mm) measured within the reported range in domestic cats (0.4-0.9 mm) 7 but lower than the reported mean in cheetahs (1.1 mm). 4 Caracals had five characteristic ultrasonographic layers of the gastrointestinal tract similar to those of domestic cats 11 and dogs.…”
Section: Discussionsupporting
confidence: 53%
“…9 The normal ultrasonographic anatomy of abdominal viscera in domestic small animal species is well documented, 1,6,7,10,11,16 providing useful reference for diagnosis of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the wall depends on angulation of the sound beam and degree of distention. 13 In our experience, most normal gallbladders in both dogs and cats are less than 1 mm. Normal thickness in dogs is reported in one study 12 as 2 to 3 mm; in another, it was found to be approximately 1 to 2 mm.…”
Section: Gallbladder Wall Thickeningmentioning
confidence: 65%
“…11 The gallbladder wall is poorly seen or appears as a thin (1 to 2 mm) echogenic line in dogs. 13 Distal acoustic enhancement is commonly seen deep to the gallbladder. 13 Distal acoustic enhancement is commonly seen deep to the gallbladder.…”
Section: Gallbladder and Biliary Systemmentioning
confidence: 99%
“…In one study an ultrasound measurement of the wall ≥1 mm was accurate in predicting gallbladder disease in cats. 14 Enlargement of the CBD can occur within 24-48 hours of acute bile duct obstruction, whereas intrahepatic biliary duct distension requires five to seven days of obstruction. Cholelithiasis can be diagnosed by ultrasonography because both radiodense and radiopaque stones can be imaged but stones within the cystic or CBD can be difficult to visualize as they are not surrounded by anechoic bile and there is the presence of interference by intestinal or gastric gas.…”
Section: Sectionmentioning
confidence: 99%